2005
DOI: 10.1007/s11240-005-3396-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome fidelity during short- and long-term tissue culture and differentially cryostored meristems of silver birch (Betula pendula)

Abstract: Clonal trueness of micropropagated or cryopreserved material is essential, especially with long-living tree species. In this study, the growth rate and morphology of regenerated silver birch (Betula pendula Roth) plants growing in the nursery were evaluated after different treatments: short-term (14 months) and longterm (70 months) tissue culture periods, cryostorage of in vivo buds and cryopreservation of in vitro shoot apices using four different slow cooling cryopreservation protocols with PGD (10% PEG, 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Representatives of Betula (birch) genus, widespread particularly in the northern parts of Eurasia and North America, are among the most important deciduous tree species in these regions (Ryynänen et al, 2005). In the coniferousdominated forests of Northern Europe, birch species (Betula pendula and B. pubescens) often grow in mixed stands with Scots pine and Norway spruce (Rytter et al, 2014), contributing significantly to the biodiversity sustention here, since birch trees provide living room for many other life forms, such as mycorrhiza-forming fungi, herbivores, wood-decaying fungi, and saproxylic insects (Hynynen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Representatives of Betula (birch) genus, widespread particularly in the northern parts of Eurasia and North America, are among the most important deciduous tree species in these regions (Ryynänen et al, 2005). In the coniferousdominated forests of Northern Europe, birch species (Betula pendula and B. pubescens) often grow in mixed stands with Scots pine and Norway spruce (Rytter et al, 2014), contributing significantly to the biodiversity sustention here, since birch trees provide living room for many other life forms, such as mycorrhiza-forming fungi, herbivores, wood-decaying fungi, and saproxylic insects (Hynynen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its ecological significance, birch is important for bioenergy production in these northern regions. Birch trees from naturally occurring and artificial plantations are also used as raw material in the manufacture of plywood and in sawmills (Ryynänen et al, 2005). Birch has a high potential for regeneration and a rapid growth rate even in poor soil; therefore it is suitable for planting in deserted agricultural lands (Walle et al, 2007) and promising for the establishement of economically valuable short rotation plantations (Hynynen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, growth rate of rice (Oryza sativa L.) and potato (Solanum tuberosum L.) plants recovered from cryopreserved tissues was found to be lower than that observed in plants from non-cryopreserved tissues (Moukadiri et al 1999;Harding and Staines 2001). However, in many other cases, no such changes in growth rates were observed (Ahuja et al 2002;Wilkinson et al 2003;Ryynanen and Aronen 2005). Karyotype studies showed that cryopreservation rarely inXicts gross changes in ploidy level (Hao et al 2002;Helliot et al 2002;Ryynanen and Aronen 2005;Urbanova et al 2002Urbanova et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many other cases, no such changes in growth rates were observed (Ahuja et al 2002;Wilkinson et al 2003;Ryynanen and Aronen 2005). Karyotype studies showed that cryopreservation rarely inXicts gross changes in ploidy level (Hao et al 2002;Helliot et al 2002;Ryynanen and Aronen 2005;Urbanova et al 2002Urbanova et al , 2006. At the genomic DNA level, microsatellite markers showed that plants produced from cryopreserved explants showed patterns similar to their non-cryopreserved counterparts (Olivares-Fuster et al 2000;Harding and Benson 2001;Richards et al 2004).…”
Section: Introductionmentioning
confidence: 99%